Peta Politik Sastra Indonesia (1908-2008) - Asep Sambodja (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
How is the political map of the Indonesian literature in the last 100 years (1908-2008)? This paper will provide a descriptive political map of the Indonesian llterature in one century of the National Awakening We know that politics plays a very important role in the development of Indonesian literary history. The 20-year cycle of political changes, for example, can clearly be seen in the categorization of generations made by the critic HB Jassin.In the colonial era, the influence of politics was shown in the works of literature, either in  those which contained the spirit of anti-colonialism during the Dutch occupation or those which, due to the very repressivesituation, employed symbolism during the Japanese occupation. In Sockarno's time, the sharp differences of ideologies nationalisim, religion and communism had directly influenced the development of Indonesian literature, both in the ideology embraced by writers and in the works they produced. This can clearly be seen in the literary polemics between writers who belonged to the Lekra (Institute of Pcople' s Cuiture), who believed in social realism, and those of Manikebu (Cultural Manifesto), who believed in universal humanism.In the time of Soeharto, the polemics between the Manikebu and Lekra writers had ceased the first half of his governance, nevertheless, in the second half it appeared again. This was indicated by the polemics about the 1995 Magsaysay Award which was given to Pramudya Ananta Toer, a Lekranovelist. The polemics was started by Taufik Ismail, a Manikebu poet.The centralistic tendency done by Soeharto's regime also invited reactions among writers, among which was the issue of revitalizing local literature, refusing Jakarta as center. Apart from that, the apolitical tendency applied by Soeharto's regim was also responded by the idea of contextual literature voiced by Arief Budiman and Ariel Heryanto.Today, in the era of reformation, Indonesian writers have enjoyed the freedom of speech, fredom of expression, and the spirit of multiculturalism. The soul of Bhinneka tunggal ika contained in the classic work of the 14th century, Empu Tantular’s kakawin Sutasoma, has been resurrected in the cultural and national life in Indonesia.